2005
DOI: 10.1007/s00441-005-1106-8
|View full text |Cite
|
Sign up to set email alerts
|

Sequence of protein expression of bone sialoprotein and osteopontin at the developing interface between repair cementum and dentin in human deciduous teeth

Abstract: Experimental periodontal regeneration studies have revealed the weak binding of repair cementum to the root surface, whereas attachment of cementum to dentin preconditioned by odontoclasts appears to be superior. The aim of this study has been, therefore, to analyze the structural and partial biochemical nature of the interface that develops between resorbed dentin and repair cementum by using human deciduous teeth as a model. Aldehyde-fixed and decalcified tooth samples were embedded in acrylic or epoxy resin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 62 publications
3
30
0
5
Order By: Relevance
“…In addition, Inubushi et al (2008) reported that US promoted early cementoblastic differentiation of immature human cementoblasts. Cementoblasts share many characteristics with osteoblasts, including similar molecular properties and the ability to promote mineralization (Matias et al 2003;Bosshardt et al 2005). Because the effects of USinduced PGE 2 in cementoblasts metabolism have not yet been raised as the subject of investigation, we thus accessed the available information about the effects of US stimulation on osteoblasts' metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Inubushi et al (2008) reported that US promoted early cementoblastic differentiation of immature human cementoblasts. Cementoblasts share many characteristics with osteoblasts, including similar molecular properties and the ability to promote mineralization (Matias et al 2003;Bosshardt et al 2005). Because the effects of USinduced PGE 2 in cementoblasts metabolism have not yet been raised as the subject of investigation, we thus accessed the available information about the effects of US stimulation on osteoblasts' metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…There have been two opinions for the etching effects. First, the etching removes a smear layer and exposes the dentinal matrix fibers, resulting in that the fibers of regenerated cementum can be easily interwoven with those of dentin, to reinforce the cemento-dentinal attachment (6,8). Second, some electron-dense substances, which inhibit the cemento-dentinal adhesion, remain on the dentin defect, but are removed by etching (6,17,21).…”
Section: Immunostainingmentioning
confidence: 99%
“…OPN is a secreted adhesive glycoprotein expressed in both mineralized and non-mineralized tissues (20). In mineralized tissues, this gene expression is relatively abundant in bone (13) but also found in dentin (9,(21)(22). Defective OPN gene in mice increases mineral content and crystallinity (23).…”
Section: Introductionmentioning
confidence: 99%
“…Also, these proteins contain an Arg-Gly-Asp (RGD) motif that mediates cell attachment/signaling via interaction with cell surface integrins and post-translational modification of phosphorylation and glycosylation. These SIBLING genes are highly expressed in mineralizing tissues related to tooth and bone development and mineralization (9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%